English ‘Treatises on Physiognomy’ c. 1500 - c. 1780 - Porter, M (1997)
Physiognomy is a ubiquitous subject of both pressing contemporary concern and genuine antiquarian early—modern interest. By examining the ways in which physiognomical treatises were read, this study reconstructs a way of looking at and listening to oneself, other people, nature and God, which I refer to throughout as the art of physiognomating. Known in manuscript form in England from at least the twelfth century onwards and probably long before, printed English ‘treatises on physiognomy’ were a small but constant feature of early modern European culture which, in part, explains the success of Lavater. Although direct translations of Continental versions, the English texts drew their physiognomical content from a handful of Greek, Arabic and medieval Latin authorities. They were owned and read by people of all ages, from a variety of different social groupings and geographical areas. Physiognomating was a multi-faceted phenomenon of the longue durée, understood by some as a natural language based on instinct, a magical knowledge based on divine revelation, a branch of natural philosophy, an aspect of medicine, moral philosophy, political science, humoral theory, astrology, fortune-telling, even game-playing. The meanings of some physical features were more or less consistently agreed upon, whilst many were also supported by physiognomical proverbs and adages. Long understood as an aspect of knowing oneself (nosce teipsum), physiognomy has much to say about early modern conceptions of gender, virtue and beauty as well as the language in which early modern people understood and experienced both their own bodies, the civility of themselves and other people, as well as the character of nature and, ultimately, God. Early modern printed expositions of physiognomical doctrine migrated through a number of generically distinct texts. This migration provides evidence of the ways in which this form of looking and listening - the inspectio sapiens/inspectio prudens - was conceived and used at different times across the period. The readers’ graffiti found in the extant copies of these texts show how physiognomating ranged from being the performance of a confessional prayer in the guise of a private medico-moral self-inspection (possibly carried outwith the aid of a looking-glass) in the earlier part of the period, to a more public form of bawdy parlour game in the later part of the period. However, it was predominantly a form of political science, a utilitarian visual ideology for those everyday ‘negotiations’ with other people, with the aim of achieving business and procreational success in what was seen by many as the hazardous realm of the ‘brutish sort’ and the public sphere. Whilst physiognomy was central to John Dee's conception of science, Francis Bacon felt it needed cleansing of superstition. Most subsequent philosophers relegated it to the realm of mere opinion. Taught to children and examined at university, physiognomy was also practised by gypsies, vagabonds, astrologers, physicians, priests, ambassadors, lawyers, teachers and parents. This physiognomical gaze was also used for the choosing of a physician, a soldier, a partner or even a hat. The most prominent feature of the early modern reconfiguration of this art of physiognomating was the dissolution of the understanding of the self and other people as a constellation of natural Aristotelian and Christian ethical entities in a more fluid, culturally constructed language drawn from the characters of everyday life.